The Supervision of Islamic Education Marketing Services at SDIT Zain Al-Muttaqin Palembang - Audina, Mia; Berlian, Zainal; Zainuri, Ahmad (The Future of Education Journal, 2024)
This research project is concerned with the supervision of Islamic education marketing services at SDIT Zain Al Muttaqin Palembang. It will present an overview of the manner in which supervision is applied at SDIT Zain Al Muttaqin with a view to enhancing the attractiveness and quality of educational services. The research employs a qualitative method with a case study approach. It was conducted through direct observation at SDIT Zain Al Muttaqin Palembang. The data were analyzed using a thematic analysis approach. Supervision maximizes the potential of promotional activities at SDIT Zain Al-Muttaqin Palembang. Supervision improves ineffective methods, saving time and money. Marketing supervision at SDIT Zain Al-Muttaqin Palembang has the following impact: A structured and continuous supervisory process can enhance the effectiveness of the marketing strategy, improve the performance of the marketing team, increase parental and prospective student satisfaction, and manage the school's positive image. Such a process can reinforce the school's position in the educational market, enhance the school's image, and ensure that the marketing activities align with the school's vision, mission, and Islamic values.